1984
DOI: 10.1007/bf00690465
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sodium bicarbonate on brain blood flow, brain water content, and blood-brain barrier in the neonatal dog

Abstract: To explore the relationship between cerebral hemorrhage in the newborn and administration of sodium bicarbonate, we gave a standard dose of sodium bicarbonate (5 mEq/kg) to neonatal dogs and then assessed changes in cerebral blood flow, brain water content, and the blood-brain barrier. This dose of sodium bicarbonate produced no increase in blood pressure or cerebral blood flow and no alteration in blood-brain barrier. However, infusion of sodium bicarbonate did cause hyperosmolality and hypernatremia and a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…The length of hyperosmolarity after NaHCO 3 infusion is unknown. Siegel et al [11] described a brief increase in blood osmolarity directly after NaHCO 3 infusion while others reported a persisting hyperosmolarity 30 min after NaHCO 3 administration [10] . The increase in CBV in our study is most likely related to cerebral vasodilatation due to hyperosmolarity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The length of hyperosmolarity after NaHCO 3 infusion is unknown. Siegel et al [11] described a brief increase in blood osmolarity directly after NaHCO 3 infusion while others reported a persisting hyperosmolarity 30 min after NaHCO 3 administration [10] . The increase in CBV in our study is most likely related to cerebral vasodilatation due to hyperosmolarity.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, single measurements of CBF after NaHCO 3 infusion showed confl icting data. In healthy adults, NaHCO 3 administration resulted in an increased CBF [7] , whereas NaHCO 3 infusion did not lead to changes in CBF in animal studies [9,10] . Lou et al [34] reported a decrease in CBF after NaHCO 3 infusion in distressed preterm infants with severe metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on neonatal dogs found that infusion of hypertonic sodium bicarbonate caused a significant reduction in brain water content [16]. Several human studies have demonstrated an increase in cerebral blood flow after sodium bicarbonate infusion [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for the high mortality rate observed with bicarbonate administration may be the additional effect of osmotic load due to the dissociation of sodium bicarbonate [16]. The increase in sodium ion concentration may worsen dehydration [17] of rats that are already somewhat dehydrated due to relative milk restriction induced by the expanded litter size study design. It is also probable that systemic bicarbonate may produce additional systemic effects leading to the higher mortality rates observed.…”
Section: Discussionmentioning
confidence: 98%